Evaluation of Proficiency Level on Microsoft Excel Among the Bachelor of Science in Accountancy Students of Mindanao State University, General Santos - Cruz, Cielo S. Dela; Juaneza Jr., Randy C.; Molina, Lowela Jane T.; Auditor, Michael G. (International Journal of Research in Interdisciplinary Studies, 2026)
Computer skills are becoming increasingly important in today's global employment market, and students are expected to possess them. These abilities include basic to advanced knowledge of Microsoft Excel. The main goal of the study was to determine the proficiency level of accounting students in terms of basic, intermediate, and advanced skills in Microsoft Excel. The study used a descriptive research design with a quantitative approach. Data were gathered from the sixty-seven respondents, first-year accountancy students from Mindanao State University-General Santos. A modified and adapted four-part survey questionnaire was administered online via Google Forms. Statistical tools used to analyze and interpret data collected are frequency count and percentage, mean and weighted mean. Almost all of the respondents have undergone ICT subjects prior to college and majority have taken spreadsheet lessons. All respondents have available technological devices and most of them have access to university ICT facilities. The findings revealed that the respondents are very familiar with both the existence and features of Microsoft Excel. The respondents were completely familiar with Microsoft Excel's purpose while being very familiar with its existence and features. The findings also revealed that the respondents have advanced proficiency with regard to Microsoft Excel’s sets of basic skills, competent proficiency when performing intermediate skills, and a developing proficiency level when executing the advanced skills. It can be concluded that the first-year Bachelor of Science in Accountancy students of Mindanao State University – General Santos must develop their Microsoft Excel skills to be competitive in the labor market.